Amphiphilic nanoparticles generate curvature in lipid membranes and shape liposome–liposome interfaces. Issue 40 (7th October 2021) - Lavagna, E.; Güven, Z. P.; Bochicchio, D.; Olgiati, F.; Stellacci, F.; Rossi, G.
Abstract : We show by molecular dynamics that amphiphilic Au nanoparticles (NP) with a diameter of 4 nm generate curvature in phosphatidylcholine lipid membranes. Abstract : We show by molecular dynamics that amphiphilic Au nanoparticles (NP) with a diameter of 4 nm generate curvature in phosphatidylcholine lipid membranes. NPs generate negative curvature when they adsorb on the membrane surface but, as they get spontaneously and progressively embedded into the membrane core, the curvature turns positive. As membrane embedding is kinetically slow, both configurations can be observed by Cryo-EM. NP-induced curvature explains the peculiar structure of liposome–liposome interfaces in presence of NPs.